Principles and practices of molecular properties : theory, modeling, and simulations - Norman, Patrick; Ruud, Kenneth; Saue, Trond (Principles and Practices of Molecular Properties: Theory, Modeling and Simulations, 2018)
A comprehensive yet accessible exploration of quantum chemical methods for the determination of molecular properties of spectroscopic relevance Molecular properties can be probed both through experiment and simulation. This book bridges these two worlds, connecting the experimentalist's macroscopic view of responses of the electromagnetic field to the theoretician's microscopic description of the molecular responses. Comprehensive in scope, it also offers conceptual illustrations of molecular response theory by means of time-dependent simulations of simple systems. This important resource in physical chemistry offers: A journey in electrodynamics from the molecular microscopic perspective to the conventional macroscopic viewpoint The construction of Hamiltonians that are appropriate for the quantum mechanical description of molecular properties Time- and frequency-domain perspectives of light-matter interactions and molecular responses of both electrons and nuclei An introduction to approximate state response theory that serves as an everyday tool for computational chemists A unified presentation of prominent molecular properties Principles and Practices of Molecular Properties: Theory, Modeling and Simulations is written by noted experts in the field. It is a guide for graduate students, postdoctoral researchers and professionals in academia and industry alike, providing a set of keys to the research literature.